Percutaneous Coronary Intervention of Bifurcation Lesion (Cardiovascular Journal, 2022)
Bifurcation lesion whether it is left main (LM) stem disease with left main to left anterior descending artery (LM-LAD) or left main to left circumflex (LM-LCX), LAD-Diagonal or LCX-Obtuse marginal or right coronary artery- posterior descending artery (RCA-PDA); are not uncommon lesion type that needs to be revascularized either by percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) to establish the coronary flow and relieved patient anginal symptoms. Even though, many of the literature maintained non-inferiority of bifurcation lesion PCI over CABG and is Class IIb indication for PCI by coronary stent. In literature, bifurcation lesions commonly encountered in PCI and are regarded as most technically challenging lesions to treat, in up to 20% of PCI cases. With the advent of interventional procedures and the availability of cardiac catheterization laboratory facilities, skilled interventionist, many of the Bangladeshi patients are being treated for coronary artery diseases (CAD). With the advent of drug eluting stents, availability of IVUS (Intravascular Ultrasound), FFR (Fractional Flow Reserve) and individual expertise, treating bifurcation lesion may not be difficult task. Interventionist must be expert enough in doing PCI, before to proceed for bifurcation lesion PCI. We need to work together to develop common consensus in developing updated skill in treating bifurcation lesion which will prove bifurcation PCI in our population.Cardiovasc j 2022; 14(2): 168-175